Poly(hydroxyalkanoate)s - Taguchi, S.; Iwata, T.; Abe, H.; Doi, Y.; S. N., Aqida (Elsevier, 2016)
Poly(hydroxyalkanoate)s (PHAs) have emerged as a family of aliphatic polyesters produced by a number of bacteria. PHAs have attracted much attention as biodegradable thermoplastics to solve the waste disposal challenge. Currently, from the viewpoint of effective utilization of natural resources, the PHAs are recognized as bio-based polymeric materials produced from renewable biomass resources. In this article, we have attempted to give an overview of research and development on biosynthesis, structure and properties, and biodegradability of PHAs, and to relate prospects of the field. In addition, the present situation regarding industrial production of PHA materials is presented.